Factors Influencing Impulsive Buying Behavior Among Public School Teachers - Mejia, Ellaiza Bhel F.; Antonio, Khent S.; Carino, Jhinverlyn V.; Villarta, Djdiosh G.; Fulong, Lorna V. (International Journal of Research in Interdisciplinary Studies, 2025)
This study investigates the factors influencing impulsive buying behavior among high school teachers in the Diadi region of Santiago City, Isabela. Impulsive buying is characterized by spontaneous, unplanned purchases often driven by emotional and psychological triggers. While teachers are generally viewed as financially stable professionals, they are not immune to impulsive spending influenced by emotional pressures, social dynamics, and professional demands. Understanding these factors is crucial in promoting responsible financial behavior among educators. Using a quantitative research design, the study collected data from 64 purposively selected public high school teachers through a validated questionnaire adapted from Barakat (2019). The instrument measured key influences, including emotional triggers, social factors, and marketing strategies, on impulsive buying tendencies. Statistical methods, including weighted mean, standard deviation, and non-parametric tests, were applied to analyze the data and identify significant relationships and differences among variables. Results showed that the majority of respondents were young adults, predominantly female, single, and holders of master's degrees, with 1 to 10 years of teaching experience. The findings indicated that impulsive buying is a frequent behavior among teachers, primarily influenced by emotional triggers and attention-grabbing sales promotions. Sales promotions emerged as the strongest factor affecting impulsive purchases, followed by cultural influences, while merchandising and service-related factors had a moderate impact. Statistical tests confirmed significant variations in impulsive buying behavior based on these factors. The study recommends implementing financial literacy programs, wellness services, and peer mentorship initiatives to support teachers in managing impulsive spending and related emotional challenges. It also suggests that future research explore additional variables, such as salary, family size, and years of service, as well as comparisons between public and private school teachers, to gain a broader understanding of financial decision-making among educators. This study contributes to the limited body of knowledge on consumer behavior in the education sector, underscoring the importance of promoting financial responsibility within this professional group.